Exoplanet characterisation through transit timing variations - Kaye, L (2023)
Transit Timing Variations (TTVs) arise in exoplanetary systems as a result of nonlinear perturbations from Keplerian orbits. Their presence provides a valuable tool for examining the characteristics and architectures of such systems and enable measurements of mass and eccentricity as well as the detection of new planets.